The Relationship of the Presidential Decree of 5 July 1950 in Guided Democracy - Sukarddin, Sukarddin; Suryaningsih, Lili (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this research is to find out more about the process by which the 1955 election results of the constituent assembly established the Constitution of the Republic of Indonesia, prompting President Soekarno to propose a return to the 1945 Constitution. This situation has basically created a danger for the safety of the country, especially regarding national unity and unity. The method used is the historical method which includes heuristics, verification, interpretation and historiography. The results of this research can be seen through the Presidential Decree of 5 July 1959, President Soekarno declared the 1945 Constitution to be re-enacted. However, in a constitutional situation where the 1945 Constitution was implemented based on this Presidential Decree, it provided an opportunity for President Soekarno to position himself as an important policy maker in the country. In this regard, a form of democracy emerged that was initiated by Soekarno, namely Guided Democracy. Even though according to Soekarno Guided Democracy is in accordance with Pancasila by demonstrating popular principles led by wisdom in representative deliberations, the implementation of Guided Democracy which is based on the 1945 Constitution, is devoid of its true aims and objectives. This caused political instability in Indonesia, which gave rise to accesses in the state administration of the Republic of Indonesia in the following periods.